Factors affecting job dissatisfaction in Asia: a systematic review - Yin Sunn, Chong; Nai Peng, Chua; Qing, Swi Zi; Binti Wan Othman, Wan Norhayati; Mohamad Yusop, Yusni; Anuar, Muharram (Human Resources Management Academic Research Society (HRMARS), 2024)
Employee job dissatisfaction is a prevalent issue arising from unmet expectations, leading to adverse perceptions and discontent. This literature review delves into the factors contributing to job dissatisfaction in 22 Asian countries from 2020 to 2024, a region characterized by rapid economic growth and digital transformation. The review classifies these factors into environmental and organizational, drawing insights from diverse studies. Environmental factors encompass job and financial insecurity, perceived low professional standing, and inadequate job recognition, while organisational factors involve issues such as inadequate remuneration, absence of occupational safety, unfavourable working culture, and detrimental managerial practices. Adhering to the PRISMA model, this systematic review curated articles from ScienceDirect and SAGE databases. Subsequent to applying inclusion and exclusion criteria, ten articles underwent comprehensive analysis. The findings underscore prominent contributors to job dissatisfaction, including client hostility, deficient incentive structures, unsatisfactory managerial assistance, and excessive workloads, across different industries in the Asian context. Comprehending these factors can assist researchers and professionals in formulating strategies to enhance job satisfaction and overall organizational efficacy.